2018
DOI: 10.1021/acsami.7b17424
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study on Surface Segregation and Anisotropy of Ni-Rich LiNi1–2yCoyMnyO2 (NCM) (y ≤ 0.1) Cathodes

Abstract: Advances in ex situ and in situ (operando) characteristic techniques have unraveled unprecedented atomic details in the electrochemical reaction of Li-ion batteries. To bridge the gap between emerging evidences and practical material development, an elaborate understanding on the electrochemical properties of cathode materials on the atomic scale is urgently needed. In this work, we perform comprehensive first-principle calculations within the density functional theory + U framework on the surface stability, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 50 publications
7
65
0
Order By: Relevance
“…The (104) facet is the predominant surface for as‐synthesized LiNiO 2 at high temperature in O‐rich environment, and thus it has been adopted as our surface model . This confirmed by an energy comparison for different surface facets as a function of the oxygen chemical potential is also given in Figure S6 (Supporting Information), as well as in our recently published work . As shown in Figure 5 a, only Li diffusions are observed in the bulk phase during 5 ps of simulation time, and there is no evidence for oxygen migration.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The (104) facet is the predominant surface for as‐synthesized LiNiO 2 at high temperature in O‐rich environment, and thus it has been adopted as our surface model . This confirmed by an energy comparison for different surface facets as a function of the oxygen chemical potential is also given in Figure S6 (Supporting Information), as well as in our recently published work . As shown in Figure 5 a, only Li diffusions are observed in the bulk phase during 5 ps of simulation time, and there is no evidence for oxygen migration.…”
Section: Resultssupporting
confidence: 76%
“…[37,38] This observation indicates a possibility that oxygen evolution can happen on crystal regions with more open space with reduced migration barrier for the oxygen atom or dimer. [40] As shown in Figure 5a, only Li diffusions are observed in the bulk phase during 5 ps of simulation time, and there is no evidence for oxygen migration. In order to investigate the effect of the available space on oxygen migration, we have compared atomic kinetics in the oxide bulk and surface regions.…”
Section: Surface Oxygen Evolution and Phase Transitionmentioning
confidence: 90%
“…Further, there are studies that show existence of additional structural phases, such as rock‐salt, which coexist with the layered structure at the surface of layered materials . It has been proposed that such rock‐salt phases form in concert with release of oxygen .…”
Section: Properties Of Ncmmentioning
confidence: 99%
“…Previous studies using density functional theory (DFT) calculations revealed the importance of the primary particle surface on cathode reactivity and cycling stability. [26][27][28][29] For example, the calculation carried out on LiCoO 2 and NMC111 determined that their equilibrium particle shapes consist of (104), (001) and (012) facets, 26,27 and the (104) family facets are more stable than the (012) facets during electrochemical cycling. Experimentally, oxygen release and thermal decomposition of LiCoO 2 were found to be facet-dependent, and structural reconstruction from the layered to spinel and rock-salt phases occurred preferably on (012) and (104) family facets, as opposed to the (001) facets.…”
Section: Introductionmentioning
confidence: 99%